2008
DOI: 10.1002/pssc.200879853
|View full text |Cite
|
Sign up to set email alerts
|

Cavity polariton dispersion of a single‐crystalline anthracene film embedded in a microcavity

Abstract: We study anisotropic behavior of cavity polaritons in an organic microcavity composed of a single crystalline anthracene film grown into the gap of the Fabry‐Perot cavity by a method through capillary action. The anisotropic response of the cavity polariton appeared on the spectra depending on the linear polarized directions; two kinds of the polarization correspond to the principal axes of anthracene crystal. Transmission spectra were measured with various thickness of the anthracene film. The peak‐shift of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 10 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…The results shown in Table II were in good agreement with those of the crystalline anthracene microcavities fabricated by the conventional melting technique. [11][12][13] Thus, we have shown that the clear cavity-polariton modes and the giant Rabi splitting energies are observed even for crystalline anthracene microcavities prepared using the solution technique. The solution technique can be applied to the fabrication of various crystalline organic microcavities.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…The results shown in Table II were in good agreement with those of the crystalline anthracene microcavities fabricated by the conventional melting technique. [11][12][13] Thus, we have shown that the clear cavity-polariton modes and the giant Rabi splitting energies are observed even for crystalline anthracene microcavities prepared using the solution technique. The solution technique can be applied to the fabrication of various crystalline organic microcavities.…”
mentioning
confidence: 65%
“…8,9) Although most reports have focused on microcavities including active layers of disordered mixtures such as J aggregates or organic molecules in a host matrix, crystalline organic microcavities have also been recently investigated in several reports. [10][11][12][13][14][15] In these works, Rabi splitting energies of up to $300 meV in single-crystalline anthracene microcavities were reported. [11][12][13] In addition, polariton lasing at RT has also been realized recently in crystalline organic microcavities.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Besides ASE and random lasing, some studies have also been reported on the coupling of excitons with photons in microcavity structureswhich is a rapidly growing field of research, in particular as far as strong coupling phenomena are concerned, which may lead to novel laser devices such as the polariton laser (Klaers et al 2010). Strong exciton-photon coupling has been demonstrated in microcavities of single crystal and thin film anthracene (Kena-Cohen et al 2008;Kondo et al 2009Kondo et al , 2008. More recently, Kéna-Cohen and Forrest observed polariton lasing at room temperature from a microcavity containing melt-grown anthracene single-crystal, with a threshold lower than the estimated threshold for conventional lasing in the same system (Kéna-Cohen et al 2010).…”
Section: Introductionmentioning
confidence: 99%